Bimetallic copper-gold nano-cluster Cu / AuNCs-coated ESM and synthetic method and application thereof

By embedding Cu and Au into the eggshell membrane, the bimetallic copper-gold nanocluster Cu/AuNCs@ESM was constructed, which solved the problems of low stability of single metal nanoclusters and difficult to control fluorescence emission, and achieved high sensitivity detection of ascorbic acid.

CN120133534APending Publication Date: 2025-06-13QUJING NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510247810.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The low stability, weak luminescence and difficult fluorescence emission to control, limiting its wide application in the field of biomedical science.

Method used

By embedding Cu and Au in the eggshell membrane, a bimetallic copper gold nanocluster Cu/AuNCs@ESM was constructed using a simple synthetic method for ascorbic acid-specific sensing detection.

Benefits of technology

A bimetallic nanocluster with stable structure, high fluorescence intensity and good sensitivity was obtained, which can analyze and detect ascorbic acid with high specificity, overcome the shortcomings of single metal nanoclusters, and realize the detection of ascorbic acid with a linear range of 1.0×10-6~1.0×10-1mol/L, with a detection limit of 33.34 nmol/L.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120133534A_ABST
    Figure CN120133534A_ABST
Patent Text Reader

Abstract

The invention relates to a bimetallic copper-gold nano-cluster Cu / AuNCs-coated ESM and a synthetic method and application thereof, and belongs to the technical field of analys.The synthetic method comprises the steps that firstly, an eggshell membrane gold nano-cluster is synthesized, then the eggshell membrane gold nano-cluster is put into a copper sulfate solution to react, then treatment is conducted through an alkaline solution, and the bimetallic copper-gold fluorescent nano-cluster Cu / AuNCs-coated ESM is generated; the Cu / AuNCs-coated ESM obtained by the synthesis method disclosed by the invention is used as a fluorescent probe, and can realize high-sensitivity and specific analysis and detection on ascorbic acid with different concentrations. AA has an obvious fluorescence enhancement effect on Cu / AuNCs (at) ESM as the fluorescent probe, the linear range of the fluorescent probe for sensing analysis of AA is 1.0 * 10 <-6 >-1.0 * 10 <-1 > mol / L, and the detection limit is 33.34 nmol / L. The bimetallic copper-gold fluorescent nano-cluster Cu / AuNCs-coated ESM fluorescent probe synthesized by the invention is stable in structure and environment-friendly, and provides a new thought and method for the development of the field of biosensing analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of analytical technology, and in particular, relates to a bimetallic copper-gold nanocluster Cu / AuNCs@ESM and a synthesis method and application thereof. Background Art

[0002] With the rapid development of nanotechnology, the development and application of nanomaterials have ushered in a broad space for development. Precious metal nanoclusters (MNCs), which serve as bridges between atoms and nanoparticles (NPs), have attracted widespread attention from scientific researchers due to their unique properties such as excellent optical properties, good biocompatibility and catalytic activity. Metal nanoclusters are relatively stable nanostructures composed of several to hundreds of metal atoms, and their size is usually at the nanometer level. These nanoclusters have unique physical and chemical properties and therefore have a wide range of applications in many fields. In the field of materials science, metal nanoclusters can be used to prepare high-performance electronic devices such as sensors, solar cells and optoelectronic devices, as well as metal composites with high strength, high electrical conductivity and high thermal conductivity. In the medical field, they can be used to prepare biosensors and drug delivery systems to treat tumors, inflammation and infectious diseases.

[0003] Metal nanoclusters also have good biocompatibility and drug carrying capacity. The fluorescence properties of metal nanoclusters are particularly noteworthy. When the size of metal particles is comparable to the Fermi wavelength of electrons, the energy levels become discontinuous due to the quantum size effect, which can stimulate electronic transitions and produce strong fluorescence. This fluorescence property has a size-dependent effect, so compared with traditional organic fluorescent dyes and quantum dots, metal nanoclusters not only have size-dependent and adjustable fluorescence, but also have higher quantum yield and fluorescence stability.

[0004] Fluorescence detection methods have the advantages of high reliability, high sensitivity, convenient operation, fast response speed, and convenient instrument requirements, and are widely used in the analysis and detection of samples. Metal nanoclusters have attracted much attention as a class of nanomaterials with unique "excimer-like" properties. Gold nanoclusters (AuNCs) have received extensive attention in the fields of basic physical chemistry and biomedical applications due to their unique electronic structure and luminescence properties. Fluorescent gold nanoclusters (AuNCs) are one of the nanomaterials with good stability among metal nanoclusters. Usually, HAuCl4·3H2O is used as a metal precursor, and thiol-containing biomolecules are selected as ligands to synthesize AuNCs with fluorescence emission in one step under appropriate reduction conditions. However, the high cost of gold and weak luminescence have hindered its wide application in biomedicine. Fluorescent copper nanoclusters (CuNCs) are mainly applied in the fields of chemical sensors, bioimaging, and light-emitting devices (LEDs), etc. However, the small size of independent fluorescent copper nanoclusters makes them easily oxidized, reducing the fluorescence stability of copper nanoclusters. At the same time, the lack of research on the fluorescence emission mechanism of copper nanoclusters also makes their fluorescence emission difficult to control. Summary of the Invention

[0005] Based on the problems proposed in the background technology, the synthesis method of the present invention embeds Cu and Au into the eggshell membrane to construct a simple, non-toxic, highly stable, and highly sensitive bimetallic fluorescent nanoprobe, and uses it for the specific sensing detection of ascorbic acid, overcoming the disadvantages of low stability, weak luminescence, and difficult control of fluorescence emission of single metal nanoclusters. In addition, the appropriate doping of copper improves the fluorescence intensity of gold nanoclusters, and at the same time, a bimetallic fluorescent nanoprobe with stable structure and environmental friendliness is obtained. When performing sensing analysis of ascorbic acid, the linear range of the sensing analysis of ascorbic acid is: 1.0×10 -6 ~1.0×10 -1 mol / L, and the detection limit is: 33.34 nmol / L.

[0006] For the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM of the present invention, the molar ratio of copper to gold is (0.33~2.5):1.

[0007] Further, for the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM, the molar ratio of copper to gold is (0.5~2.5):1.

[0008] Further, for the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM, copper and gold are embedded in the eggshell membrane.

[0009] The synthesis method of the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM is as follows: First, the eggshell membrane is put into chloroauric acid solution for reaction to obtain eggshell membrane gold nanoclusters AuNCs@ESM. Then, the eggshell membrane gold nanoclusters AuNCs@ESM are further put into copper sulfate solution for reaction to obtain bimetallic copper-gold nanoclusters Cu / AuNCs@ESM, which specifically includes the following steps: (1) Put the eggshell membrane ESM into chloroauric acid solution with a concentration of 0.1~1.0 mmol / L, stir at room temperature to adsorb Au(III) ions on the eggshell membrane, and obtain eggshell membrane gold nanoclusters AuNCs@ESM with an orange-red fluorescence signal; (2) After rinsing with deionized water, put the eggshell membrane gold nanoclusters AuNCs@ESM into copper sulfate pentahydrate solution with a concentration of 0.5~1.5 mmol / L, stir and react at room temperature. After the reaction, rinse with deionized water to remove the residual solution, and then place the treated eggshell membrane in NaOH solution with a concentration of 80~100 mmol / L overnight; (3) Take out the treated eggshell membrane, wash and dry it to obtain bimetallic copper-gold nanoclusters Cu / AuNCs@ESM with a strong red fluorescence.

[0010] Further, before the reaction in step (1), the eggshell membrane is first purified and dried.

[0011] Specifically, the purification and drying of the eggshell membrane refer to treating the eggshell in the following steps: washing it clean with deionized water, soaking it in deionized water for 1.5~4.0 h, soaking it in dilute hydrochloric acid solution for 15~40 min, rinsing with deionized water, peeling off the eggshell membrane and rinsing it with deionized water, and drying it in a vacuum drying oven at 30~60 °C for 0.5~1.5 h.

[0012] Further, the drying temperature of the eggshell membrane in step (3) is 30~60 °C.

[0013] The present invention also provides bimetallic copper-gold nanoclusters Cu / AuNCs@ESM obtained by the above synthesis method.

[0014] The present invention also provides the application of bimetallic copper-gold nanoclusters Cu / AuNCs@ESM as a fluorescent probe.

[0015] The present invention also provides the application of bimetallic copper-gold nanoclusters Cu / AuNCs@ESM as a fluorescent probe in detecting ascorbic acid.

[0016] Further, the linear range of the sensing analysis of Cu / AuNCs@ESM for ascorbic acid is 1.0×10 -6 ~1.0×10 -1 mol / L Advantages of the invention: The synthesis method of the present invention obtains a brand-new bimetallic nanocluster. The synthesis method has low requirements for equipment and is environmentally friendly. The synthesized bimetallic copper-gold nanocluster Cu / AuNCs@ESM has a stable structure and strong red fluorescence. As a fluorescent probe, it has good stability and high sensitivity, and can specifically analyze and detect ascorbic acid. Experiments have proved that when the bimetallic copper-gold nanocluster Cu / AuNCs@ESM is used as a fluorescent probe, it has good fluorescence stability, overcoming the disadvantages of weak luminescence, poor stability and difficult control of fluorescence emission of single-metal nanoclusters. The linear range of the obtained bimetallic fluorescence sensor for the sensing analysis of ascorbic acid is: 1.0×10 -6 ~1.0×10 -1 mol / L, and the detection limit is: 33.34 nmol / L. Description of the drawings

[0017] Figure 1 is a schematic diagram of the synthesis process of the bimetallic fluorescent probe provided by the embodiment of the present invention; Figure 2 is the SEM diagram of ESM, Cu / AuNCs@ESM in Example 1 of the present invention, and AuNCs@ESM of Comparative Example 1. Figure A is ESM, Figure B is AuNCs@ESM, and Figure C is Cu / AuNCs@ESM; Figure 3 is the Au 4f XPS spectrum of Cu / AuNCs@ESM in Example 1 of the present invention; Figure 4 is the Cu 2p XPS spectrum of Cu / AuNCs@ESM in Example 1 of the present invention; Figure 5 is the infrared spectrum of ESM and Cu / AuNCs@ESM in Example 1 of the present invention, and AuNCs@ESM of Comparative Example 1; Figure 6 is the solid-state ultraviolet-visible spectrum of Cu / AuNCs@ESM in Example 1 of the present invention and AuNCs@ESM of Comparative Example 1; Figure 7 is the fluorescence intensity comparison diagram of Cu / AuNCs@ESM, ESM in Example 1 of the present invention, and AuNCs@ESM of Comparative Example 1. (a) is Cu / AuNCs@ESM, (b) is AuNCs@ESM, and (c) is ESM; Figure 8 is the response diagram of Cu / AuNCs@ESM in Example 1 of the present invention to ascorbic acid solutions with different concentrations; Figure 9 is the linear diagram of ascorbic acid detection by Cu / AuNCs@ESM in Example 1 of the present invention.

[0018] Figure 10 It is a comparative graph of the fluorescence intensities of Cu / AuNCs@ESM of Example 1 of the present invention, AuNCs@ESM of Comparative Example 1, and CuNCs@ESM of Comparative Example 2; Figure 11 It is a fluorescence intensity graph of Cu / AuNCs@ESM with different copper-gold molar ratios in Example 2 of the present invention. Detailed implementation manners

[0019] In order to make the objectives, technical solutions, and beneficial effects of the present invention clearer, the technical solutions of the present invention will be described in detail below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative efforts fall within the protection scope of the present invention.

[0020] The synthesis method of the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM includes the following steps: (1) Clean the collected eggshells with deionized water, soak them in pure water for 1.5 - 4.0 h, then soak them in a 0.1 mmol / L hydrochloric acid solution for 15 - 40 min. After rinsing with deionized water, peel off the eggshell membrane (ESM) and rinse it twice with deionized water. After rinsing, continue to soak it in a 0.1 mmol / L hydrochloric acid solution for 15 - 40 min. Finally, take out the ESM, wash it with deionized water, and dry it in a vacuum drying oven at 30 - 60 °C for 1.5 - 4.0 h.

[0021] (2) Put the ESM obtained in step (1) into 30 mL of a chloroauric acid (HAuCl 4 ·3H 2 O) solution with a concentration of 0.2 - 1.0 mmol / L, stir at a rate of 500 - 800 r / min at room temperature for 5 - 20 min. Au(III) ions are easily adsorbed on the ESM. The ESM slowly changes from white to light yellow after contacting with the HAuCl 4 solution, and finally the ESM gradually turns dark brown. Take out the treated eggshell membrane and rinse it two to three times with deionized water to remove the residual solution, and obtain eggshell membrane gold nanoclusters (AuNCs@ESM) with an orange fluorescence signal.

[0022] (3) Put the eggshell membrane gold nanoclusters (AuNCs@ESM) obtained in step (2) into 30 mL of a copper sulfate (CuSO 4 ·5H 2In an O) solution, stir at a rate of 500 - 800 r / min for 5 - 20 min at room temperature, then rinse with deionized water two to three times to remove the residual solution. Then place it in 50 mL of a NaOH solution with a concentration of 80 - 100 mmol / L and let it stand overnight. Take out the treated eggshell membrane, wash it with deionized water, and dry it in a vacuum drying oven at 30 - 60 °C for 0.5 - 1.5 h to obtain bimetallic copper-gold nanoclusters (Cu / AuNCs@ESM) with strong red fluorescence.

[0023] To illustrate the present invention more clearly, the following examples are provided for detailed description. Example 1

[0024] The synthesis method of bimetallic copper-gold nanoclusters Cu / AuNCs@ESM is as follows: Wash the collected eggshells with deionized water, soak them in pure water for 3 h, then soak them in a 0.1 mmol / L hydrochloric acid solution for 30 min. After rinsing with deionized water, peel off the eggshell membrane (ESM), and then rinse it twice with deionized water. After rinsing, soak the eggshell membrane in a 0.1 mmol / L hydrochloric acid solution for 30 min. Finally, take out the eggshell membrane, wash it with deionized water, and dry it in a vacuum drying oven at 60 °C for 3 h to obtain the treated ESM. Divide the ESM into two parts, one part is reserved for the following performance comparison test, and the other part is processed as follows: Put the dried ESM into 30 mL of a chloroauric acid (HAuCl 4 ) solution with a concentration of 0.5 mmol / L, stir at a rate of 600 r / min at room temperature for 10 min. The ESM slowly changes from white to light yellow after contacting with the HAuCl 4 solution, and finally the ESM gradually turns dark brown. Take out the eggshell membrane, and then rinse it two to three times with deionized water to remove the residual solution; put the treated eggshell membrane into 30 mL of a copper sulfate (CuSO 4 ) solution with a concentration of 1.0 mmol / L, stir at a rate of 600 r / min at room temperature for 10 min, then rinse it two to three times with deionized water to remove the residual solution. Then place the treated eggshell membrane in 50 mL of a NaOH solution with a concentration of 90 mmol / L and let it stand for 24 h. Take out the eggshell membrane, wash it, and dry it in a vacuum drying oven at 60 °C for 1 h to obtain bimetallic copper-gold nanoclusters (Cu / AuNCs@ESM) with strong red fluorescence.

[0025] Comparative Example 1

[0026] The synthesis method of eggshell membrane gold nanoclusters AuNCs@ESM The collected eggshells were washed clean with deionized water and soaked in pure water for 3 h, then soaked in 0.1 mmol / L hydrochloric acid solution for 30 min. After rinsing with deionized water, the eggshell membrane (ESM) was peeled off and rinsed twice with deionized water. After rinsing, the eggshell membrane was soaked in 0.1 mmol / L hydrochloric acid solution for 30 min. Finally, the eggshell membrane was taken out, washed with deionized water, and dried in a vacuum drying oven at 60 °C for 3 h to obtain the treated ESM. The ESM was divided into two parts. One part was reserved for the following performance comparison test, and the other part was processed as follows: The dried ESM was placed in 30 mL of chloroauric acid (HAuCl 4 4) solution with a concentration of 0.5 mmol / L and stirred at a rate of 600 r / min at room temperature for 10 min. The ESM slowly changed from white to light yellow after contacting with the HAuCl 4 solution, and finally the ESM gradually changed to dark brown. Then the treated eggshell membrane was rinsed with deionized water two to three times to remove the residual solution and dried in a vacuum drying oven at 60 °C for 1 h to obtain eggshell membrane gold nanoclusters (AuNCs@ESM) with orange-red fluorescence signal.

[0027] Physical property analysis:

[0028] SEM, AuNCs@ESM, and Cu / AuNCs@ESM obtained in Example 1 and Comparative Example 1 were scanned by electron microscopy. The results are as Figure 2 shown ( Figure 2 in which Figure A is ESM, Figure B is AuNCs@ESM, and Figure C is Cu / AuNCs@ESM). It can be seen from the electron micrographs that the inner surface of SEM is composed of a complex fiber lattice network. The distribution of embedded bimetallic Cu / AuNCs is more compact than that of embedded monometallic Au nanoclusters, and the morphological structure is more stable. The nanoclusters Cu / AuNCs are tightly deposited on the surface of ESM fibers, constituting a Cu / AuNCs@ESM fluorescence probe with good biocompatibility and stability.

[0029] Figure 3 And Figure 4 are the XPS spectra of Au 4f and Cu 2p of the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM, respectively. It can be Figure 3 seen that Au 4f in Cu / AuNCs@ESM may consist of two valence states, possibly because the aldehyde groups, the reducing substances contained in ESM, reduce Au(III) to Au(0) or Au(I). And Figure 4Among them, the absorption peaks in the Cu 2p of Cu / AuNCs@ESM may be due to the reduction of Cu(II) to Cu(0), and it is not excluded that copper ions form chemical bonds with certain elements in ESM or form complexes with chemical substances, resulting in additional absorption peaks. It can be speculated from the infrared-visible spectrogram (attached Figure 5 ), the functional groups of ESM and the changes in functional groups after embedding different substances. It can be observed from the ultraviolet-visible spectrogram (attached Figure 6 ) that Cu / AuNCs@ESM produces a large absorption peak at 365 nm in the ultraviolet spectrogram. At the same time, it can be judged that there are conjugated double bonds in Cu / AuNCs@ESM, which can enhance the delocalization of electrons. Fluorescence spectral test analysis was carried out on Cu / AuNCs@ESM, AuNCs@ESM and ESM, as shown in the attachment Figure 7 ( Figure 7 in which a is Cu / AuNCs@ESM, b is AuNCs@ESM, and c is ESM). It can be seen from the attachment Figure 7 that the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM have strong red fluorescence, and the fluorescence intensity is significantly stronger than that of AuNCs@ESM.

[0030] Comparative Example 2

[0031] The collected eggshells were washed clean with deionized water and soaked in pure water for 3 h, then soaked in 0.1 mmol / L hydrochloric acid solution for 30 min. After rinsing with deionized water, the eggshell membrane (ESM) was peeled off and then rinsed twice with deionized water. After rinsing, the eggshell membrane was soaked in 0.1 mmol / L hydrochloric acid solution for 30 min. Finally, the eggshell membrane was taken out, washed with deionized water, and dried in a vacuum drying oven at 60 °C for 3 h to obtain the treated ESM. The ESM was divided into two parts, one part was reserved for the following performance comparison test, and the other part was processed as follows: The dried eggshell membrane was put into 30 mL of a copper sulfate (CuSO 4 ) solution with a concentration of 1.0 mmol / L, stirred at a rate of 600 r / min for 10 min at room temperature, then rinsed with deionized water two to three times to remove the residual solution, and then the treated eggshell membrane was placed in 50 mL of a NaOH solution with a concentration of 90 mmol / L for 24 h. After taking out the ESM, washing it, and drying it in a vacuum drying oven at 60 °C for 1 h, eggshell membrane copper-gold nanoclusters (CuNCs@ESM) were obtained.

[0032] By performing fluorescence spectral test analysis on Cu / AuNCs@ESM, AuNCs@ESM and CuNCs@ESM, as shown in the attachment Figure 10 , from the attachment Figure 10It can be seen that the fluorescence intensity of CuNCs@ESM is extremely weak and it cannot be used as a fluorescence probe; AuNCs@ESM has a certain fluorescence intensity, but it is significantly weaker than that of Cu / AuNCs@ESM. As a fluorescence probe for analyzing and detecting ascorbic acid, its sensitivity is not high enough. Based on the physical property analysis of Cu / AuNCs@ESM, AuNCs@ESM and CuNCs@ESM, we select Cu / AuNCs@ESM with strong fluorescence intensity as the fluorescence probe for ascorbic acid analysis to ensure the sensitivity of the analysis and detection. Drop 0.1 mol / L ascorbic acid solution onto Cu / AuNCs@ESM respectively. After the liquid on the surface of Cu / AuNCs@ESM dries up, use a triple-purpose ultraviolet analyzer to perform ultraviolet irradiation at a wavelength of 365 nm, and preliminarily observe the change of fluorescence effect. It is found that there is an obvious change in the fluorescence intensity of Cu / AuNCs@ESM.

[0033] Drop a series of ascorbic acid solutions with different concentration gradients onto Cu / AuNCs@ESM respectively, scan on a fluorescence spectrometer, and measure the fluorescence signal intensity of ascorbic acid solutions with different concentrations on Cu / AuNCs@ESM, as Figure 8 shown. As can be seen from the appendix Figure 8 : When the concentration of the ascorbic acid solution is the maximum concentration of 0.1 mol / L, the fluorescence signal intensity of Cu / AuNCs@ESM is also the strongest.

[0034] Appendix Figure 9 is the linear graph of the fluorescence intensity detected by Cu / AuNCs@ESM when the detection range of ascorbic acid concentration is between 1.0×10 -6 ~1.0×10 -1 mol / L. The corresponding linear equation within the detection range of ascorbic acid is Y = 449.9X + 9657, and the linear correlation coefficient (R 2 ) is 0.9897, and the detection limit can reach 33.34 nmol / L. Thus, it can be seen that Cu / AuNCs@ESM has a significant response effect as a fluorescence probe for ascorbic acid. The bimetallic copper-gold nanocluster Cu / AuNCs@ESM has extremely high sensitivity and stability as a fluorescence probe for ascorbic acid detection. Example 2

[0035] The test steps of this example are the same as those of Example 1, and the treatment process and dosage of the eggshell membrane are the same as those of Example 1. During the test process, adjust the concentration and dosage of chloroauric acid (HAuCl 4 ) solution within the range of 0.1~1.0 mmol / L and 10 - 100 mL, and adjust the concentration and dosage of copper sulfate (CuSO 4 ) solution within the dosage range of 0.5~1.5 mmol / L and 10 - 100 mL.

[0036] Experimental results show that, following the steps of Example 1, within the concentration range of chloroauric acid (HAuCl 4 ), from 0.1 to 1.0 mmol / L, and copper sulfate solution concentration range, from 0.5 to 1.5 mmol / L, Cu / AuNCs@ESM bimetallic nanoclusters can be obtained. The difference lies in that the concentrations and dosages of chloroauric acid (HAuCl 4 ), and copper sulfate (CuSO 4 ), solutions will affect the molar ratio of copper to gold in the resulting bimetallic copper-gold nanoclusters Cu / AuNCs@ESM product. In this example, by adjusting the concentrations and dosages of chloroauric acid (HAuCl 4 ), and copper sulfate (CuSO 4 ), solutions, Cu / AuNCs@ESM with different copper-gold molar ratios were obtained.

[0037] The inventors performed fluorescence analysis on the obtained Cu / AuNCs@ESM with different copper-gold molar ratios and compared the fluorescence intensities with those of gold nanoclusters (AuNCs@ESM) and copper nanoclusters (CuNCs@ESM). (The results are shown in Figure 11 ), Figure 11 in the ratio of Cu 2+ : Au 3+ ). The results show that when the copper-gold molar ratio is in the range of (0.33 - 2.5):1, the resulting bimetallic nanoclusters Cu / AuNCs@ESM have higher fluorescence intensity than copper nanoclusters; when the copper-gold molar ratio is in the range of (0.5 - 2.5):1, the resulting bimetallic nanoclusters Cu / AuNCs@ESM have higher fluorescence intensity than gold nanoclusters; when the copper-gold molar ratio is 2:1, the fluorescence intensity of the resulting bimetallic nanoclusters Cu / AuNCs@ESM is the highest and significantly higher than that of other groups.

[0038] In addition, it should be noted that for the drying of the eggshell membrane in this application, as well as all the drying steps involved, the drying temperature is not a critical control index, as long as the temperature does not cause charring or physical property changes in the eggshell membrane. Also, the drying method of this application does not necessarily need to be carried out under vacuum conditions. The vacuum drying method was adopted in the example because vacuum can improve the drying speed. The control index for the drying process is based on temperature control, and the control of vacuum degree should not be regarded as a limitation to the preparation method of this application. In addition, there are no strict requirements for the treatment time of the eggshell membrane, the concentration of hydrochloric acid for soaking, etc., as long as the eggshell and impurities in the eggshell membrane can be soaked off. The soaking time of the eggshell membrane and the concentration of hydrochloric acid for soaking should not be regarded as a limitation to the preparation method of this application.

[0039] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit them. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A bimetallic copper-gold nanocluster Cu / AuNCs@ESM, characterized in that: The molar ratio of copper to gold in the bimetallic copper-gold nanocluster Cu / AuNCs@ESM is 0.33-2.5:

1.

2. The bimetallic copper-gold nanocluster Cu / AuNCs@ESM according to claim 1, characterized in that: The molar ratio of copper to gold in the bimetallic copper-gold nanocluster Cu / AuNCs@ESM is 0.5-2.5:

1.

3. The bimetallic copper-gold nanocluster Cu / AuNCs@ESM according to claim 1 or 2, characterized in that: In the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM, copper and gold are embedded in the eggshell membrane.

4. The method for synthesizing bimetallic copper-gold nanoclusters Cu / AuNCs@ESM according to any one of claims 1 to 3, characterized in that: The eggshell membrane is first placed in a chloroauric acid solution to react to obtain eggshell membrane gold nanoclusters AuNCs@ESM, and the eggshell membrane gold nanoclusters AuNCs@ESM are further placed in a copper sulfate solution to react to obtain bimetallic copper-gold nanoclusters Cu / AuNCs@ESM.

5. The synthesis method according to claim 4, characterized in that The following steps are involved: (1) The eggshell membrane (ESM) was placed in a 0.1-1.0 mmol / L chloroauric acid solution and stirred at room temperature to allow Au (III) ions to adsorb on the eggshell membrane, thereby obtaining eggshell membrane gold nanoclusters (AuNCs@ESM) with orange-red fluorescence signals. (2) After rinsing with deionized water, the eggshell membrane gold nanoclusters AuNCs@ESM were placed in a 0.5-1.5 mmol / L copper sulfate pentahydrate solution and stirred for reaction. After the reaction was completed, the residual solution was removed by rinsing with deionized water, and the eggshell membrane was placed in a 80-100 mmol / L NaOH solution overnight. (3) The eggshell membrane was removed, washed with deionized water, and then dried to obtain bimetallic copper-gold nanoclusters Cu / AuNCs@ESM with strong red fluorescence.

6. The synthesis method according to claim 5, characterized in that The eggshell membranes described in step (1) are firstly cleaned from impurities and dried before the reaction in step (1) is carried out.

7. The synthesis method according to claim 6, characterized in that The impurity removal and drying of the eggshell membrane specifically refers to treating the eggshell in the following steps in sequence: cleaning with deionized water, soaking in deionized water for 1.5 to 4.0 hours, soaking in a dilute hydrochloric acid solution for 15 to 40 minutes, rinsing with deionized water, peeling off the eggshell membrane and rinsing with deionized water, and drying in a vacuum drying oven at 30 to 60°C for 0.5 to 1.5 hours.

8. The bimetallic copper-gold nanoclusters Cu / AuNCs@ESM obtained by the synthesis method according to any one of claims 5 to 7.

9. Use of the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM as claimed in claim 8 as a fluorescent probe.

10. Use of the bimetallic copper-gold nanoclusters Cu / AuNCs@ESM as claimed in claim 8 as a fluorescent probe in detecting ascorbic acid.

Citation Information

Patent Citations

  • Red fluorescent gold / copper nanocluster alloy as well as preparation method and application thereof

    CN105199718A

  • Preparation method of chicken protein protection gold-copper nano-cluster and application of chicken protein protection gold-copper nano-cluster in mercury ion detection

    CN114689557A

  • Precious metal-eggshell membrane photo-thermal material as well as preparation method and application thereof

    CN115212306A

  • Application of copper-gold nano-cluster / carbon quantum dot ratiometric fluorescent probe in detection of aflatoxin

    CN118909622A

  • Gold nanocluster complex and method for producing same

    KR1020150008661A